Mobile Money and the Economy : A Review of Evidence - Aron, Janine (Published by Oxford University Press on behalf of the World Bank, 2020)
Mobile money is a recent innovation that provides financial transaction services via mobile phone, including to the unbanked global poor. The technology has spread rapidly in the developing world, “leapfrogging” the provision of formal banking services by solving the problems of weak institutional infrastructure and the cost structure of conventional banking. This article examines the evolution of mobile money and its important role in widening financial inclusion. It explores the channels of economic influence of mobile money from a micro perspective, and critically reviews the empirical literature on the economic impact of mobile money. The evidence convincingly suggests that mobile money fosters risk-sharing, but direct evidence of the promotion of welfare and saving is still mostly rather less robust.